Enkindling Love : The Legacy of Teresa of Avila and John of the Cross - Ahlgren, Gillian T. W., 1964- (Mapping the tradition., 2016)
Enkindling Love chronicles the journey toward a living partnership with God, as articulated by two of Christianity' great mystical teachers. Excerpts from the seven moradas (dwelling places) of Teresa of Avila's Interior Castle are held together with selections from John of the Cross's Dark Night of the Soul, Spiritual Canticle, and The Living Flame of Love, in order to show stages of growth and transformation as this partnership moves from its nascent potential through deepening friendship and intimacy to the full fruition of the mystical life. Moving through the process via textual passages and commentary, readers are invited to consider God's desire for partnership with us and how the love of God actively invites us into deeper relationship not only with God but also with self and other. Because Teresa and John experienced God's love as a transforming power, they teach that it is a participatory reality that shapes and remakes us, even as if invites us to collaborate with God in the remaking of our world.